2020
DOI: 10.1080/19331681.2019.1710318
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a post? How sentiment and issue salience affect users’ emotional reactions on Facebook

Abstract: We investigate the effects of sentiment and issue salience on emotionally labeled responses to posts from political actors on Facebook (i.e., Reactions). We use an automated content analysis of Facebook posts and voter survey data in a multilevel negative binomial regression approach. Findings show that the sentiment of a post relates to the number of "Love" and "Angry" Reactions. Furthermore, if a post addresses an issue that constituents perceive as salient, this positively influences the number of "Angry" R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 70 publications
6
62
3
Order By: Relevance
“…Although previous research indicates that the love reaction is used in a largely monosemantic positive way ( 37 ), the nature of anger reactions toward articles is less clear as readers may simply be expressing anger at the death of an individual rather than at the content of an article. Importantly, however, previous research has identified anger as a strong motivating factor for sharing of information by individuals ( 38 ), yet our findings diverge from this as articles with the highest safe-reporting scores and resharing had the lowest odds of anger reactions. This suggests that the expression of anger in relation to suicide-related news and resultant social actions are a nuanced area that merits further research.…”
Section: Discussioncontrasting
confidence: 99%
“…Although previous research indicates that the love reaction is used in a largely monosemantic positive way ( 37 ), the nature of anger reactions toward articles is less clear as readers may simply be expressing anger at the death of an individual rather than at the content of an article. Importantly, however, previous research has identified anger as a strong motivating factor for sharing of information by individuals ( 38 ), yet our findings diverge from this as articles with the highest safe-reporting scores and resharing had the lowest odds of anger reactions. This suggests that the expression of anger in relation to suicide-related news and resultant social actions are a nuanced area that merits further research.…”
Section: Discussioncontrasting
confidence: 99%
“…First, they convey a clear emotional connotation about how Facebook users respond to specific pieces of content. Indeed, Eberl et al (2020) show that these reactions are correlated as expected with the sentiment expressed in post texts, which differs from the much more ambiguous Like reactions (Gerlitz and Helmond, 2013). Like reactions are a signal of support for a post, but can convey wildly different emotions depending on the specific content.…”
mentioning
confidence: 66%
“…In many cases the content of the post seems to be a driving factor with, for instance, angry rhetoric garnering Angry reactions (Eberl et al, 2020). However, these examples also…”
Section: How Facebook Reactions Reflect Emotional Responsesmentioning
confidence: 99%
“…In this paper, user identity is a binary value, with 1 for users with identity and 0 for others. A user’s influence is measured by the number of followers, and in social media, the number of followers is a visual indicator of a user’s influence within the platform [ 66 , 67 ]. Since a small number of users have a much larger number of followers than the average, we took the logarithm of the number of followers in order to avoid problems caused by data deviation.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, when a poster has a title, it enhances the authenticity of their identity. In terms of a user’s influence, simple cues, such as the number of followers, can imply the influence of a user within the community [ 66 , 67 ]. For example, a user’s number of followers can give an indication of how many people will see the message posted by them.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%